Sense of purpose in life vs. creative activity motivators in senior managers = Motywatory twórczej aktywności a poczucie sensu życia u menedżerów - Mróz, Barbara (Zielona Góra: Faculty of Economics and Management Press)
The motivators being the subject matter of the research conducted in the 1999 and 2010 groups of managers were analysed in the context of the sense of purpose in life. Application of various motivators offers a greater opportunity to achieve better results of subordinates' work. Strong motivation ensures perseverance in actions taken. A well-motivated employee displays resistance to tiredness and strives to attain goals set by his/her company?s management.
Keywords: menedżerowie; motywatory; poczucie sensu czasu; senior managers; motivators; sens of purpose in life